Teaching of Mathematics and Physics in Secondary School through Research and Study Paths - Otero, Maria Rita (2015)
In this paper we present a proposal for teaching based on the Research and Study Paths (RSP) involving Mathematics and Physics together at the Secondary School. We adopt the ideas of the Anthropological Theory of didactic (ATD). The Research and Study Path (RSP) and the Praxeological Model of Reference (PMR) are described and analyzed. We carried out an implementation with N=68 students of 5th year at the secondary school. Some results obtained in this experience are described.